Fair Value of Earnouts: Valuation Uncertainty or Managerial Opportunism? - Ferguson, Andrew; Hu, Cecilia Wei; Lam, Peter (The Accounting Review, 2024)
ABSTRACT This study investigates the economic consequences of the IFRS 3 (2008) requirement for fair valuing earnouts. Using a hand-collected sample of earnout fair value estimates in acquisitions completed by Australian firms, we find that a significant portion of acquirers overstate initial earnout liabilities and strategically reverse them as operating gains to boost post-M&A earnings. These overstatements are more pronounced when acquirers face investment- and performance-related pressure but attenuated in the presence of high-quality auditors and debt-financed deals. Acquirers also obfuscate earnout-related disclosures, inhibiting investors’ assessment of earnout values. By doing so, managers extend their tenure. Further analysis reveals that IFRS 3 (2008) leads to a significant increase in both the frequency and magnitude of earnouts in public acquirers’ transactions. Overall, we highlight the accounting benefit of earnouts for acquirers under IFRS 3 (2008), with implications for investors, analysts, auditors, and standard setters. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: G34; M41.